Development and validation of QoL5 for clinical databases. A short, global and generic questionnaire based on an integrated theory of the quality of life - Lindholt, Jes S.; Ventegodt, Søren; Henneberg, Eskild W. (The European journal of surgery, 2002)
Objective: To develop and validate a short, global, and generic quality of life (QoL) questionnaire for clinical databases. The construct validity and item weighting of existing questionnaires are increasingly questioned. Design: Cross‐sectional population study. Subject: 2460 Danes aged 18–88 years, randomly selected through the Danish Central Person Registry. Interventions: Ten questions covering the spectrum of the integrative theory of QoL together with the Nottingham Health Profile (NHP), Sickness Impact Profile (SIP), and self‐estimated QoL questionnaire were sent by mail. A test‐retest study of 50 people was conducted after one month. Main outcome measures: Construct and criterion validity, reliability, and sensitivity. Results: QoL5 correlations with SIP, NHP, Self‐estimated QoL were 0.37, 0.52, and 0.76, respectively, and increased among those who were unwell. Cronbach's α was 0.69. All correlations in Siegel's test were over 0.6, and the test‐retest correlation was 0.82. Only 12 respondents in each group will be needed to detect a difference of 10% in the QoL score between two groups. Conclusions: QoL5 is a valid global and generic QoL measurement. Despite the use of only five questions, internal consistency and sensitivity were acceptable. So a relevant and practical outcome measurement is available for clinical databases. Copyright © 2002 Taylor and Francis Ltd.